2019
DOI: 10.1080/09537325.2019.1648788
|View full text |Cite
|
Sign up to set email alerts
|

Technology legitimation in the public discourse: applying the pillars of legitimacy on GM food

Abstract: The public sphere, reflected by the public discourse, is an important domain for the legitimation of technology. In the institutional literature, four pillars of legitimacy are distinguished: normative, cognitive, regulative, and pragmatic. The aim of this study was to investigate to what extent these pillars can be used as a framework for analysing the legitimation of technological innovations in the public discourse. We conducted a qualitative media analysis of the case of GM food in the Netherlands, analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This sees legitimacy as being in flux, in a constant process of legitimation and de-legitimation (Binz et al 2016;Geels and Verhees 2011;Suddaby et al 2017). Legitimacy is not a static property but is rather formed as an element of an active and continuous process, where actors can take from a number of strategies in order to increase or reduce the legitimacy of certain technologies (Geels and Verhees 2011;Jansma et al 2020;Suchman 1995).…”
Section: Technology Legitimacymentioning
confidence: 99%
See 1 more Smart Citation
“…This sees legitimacy as being in flux, in a constant process of legitimation and de-legitimation (Binz et al 2016;Geels and Verhees 2011;Suddaby et al 2017). Legitimacy is not a static property but is rather formed as an element of an active and continuous process, where actors can take from a number of strategies in order to increase or reduce the legitimacy of certain technologies (Geels and Verhees 2011;Jansma et al 2020;Suchman 1995).…”
Section: Technology Legitimacymentioning
confidence: 99%
“…Scott 2021). These approaches might also offer a way to disrupt (Marberg et al 2017) or GMO crops (Jansma et al 2020). Change the public perception of GMO crops (normative & cognitive legitimacy) (Jansma et al 2020) the socio-technical regime by disrupting current institutional structures and by contesting the ideas that help maintain these institutions (Frank and Schanz 2022;Geels and Verhees 2011).…”
Section: Knowledge Claims For Legitimacymentioning
confidence: 99%
“…Once legitimated, they can drive diffusion of information. Awareness or knowledge about the technological innovation is typically achieved through information exchange in heterophile groups [6].…”
Section: Covid-19 As An Exogenous Force Influencing Technology Adoption and Diffusionmentioning
confidence: 99%
“…Consumer values related to gene marking technology are of paramount interest and importance for science and industry stakeholders, given the changing standards of the modern consumer. Past research has shown that public acceptance of GM in food production is relatively low overall (Frewer et al, 2004;Jansma et al, 2019). However, it is not known how the public would perceive the use of GM in a food production process that results in a non-GM food product.…”
Section: Present Studymentioning
confidence: 99%